A Study on the Availability of Physical Facilities and Extra-curricular Activities in Public School in Kathmandu District - Shrestha, Shrestha, Mitralal, Rajkumar (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
Schools are intended to cultivate and foster a student's complete potential, nurturing their physical, intellectual, and moral development through guidance and support. Hence, Schools provide physical and non-physical facilities, especially extracurricular activities. The primary purpose of this paper was to study on the availability of physical facilities and extra-curricular activities in public schools in Kathmandu district. This research is a quantitative study with data collection techniques by means of observation, interviews, and documentation.